Factors contributing to the imbalances of cargo flows in Malaysia large-scale minor ports using a fuzzy analytical hierarchy process (FAHP) approach - Othman, Mohammad Khairuddin; Abdul Rahman, Noorul Shaiful Fitri; Ismail, Alisha; Saharuddin, A.H. (2020)
Malaysian ports have been recording imbalances in cargo flows year after year, whether in the form of a deficit or surplus, and the condition is becoming significant. As such, it has raised concerns among port stakeholders about the impact of such a situation on the sustainability of port operations, as well as questions about the actual reasons behind the occurrence, which is still ambiguous with regard to large-scale minor ports in Malaysia. This study was aimed at identifying the main factors that are contributing to the imbalanced cargo flows at large-scale minor ports in Malaysia by ranking all the possible factors using a systematic decision-making technique known as FAHP. The results showed that “economic factors” are the main contributors to these imbalances, followed by several other factors. This study contributes a clear insight into the main factors that are causing the imbalances in cargo flows at large-scale minor ports in Malaysia. Also, it may assist decision-makers and policymakers in identifying the key factors that are affecting business operations at these ports as well as guide them into using a systematic analytical approach like the FAHP to evaluate other situations with regard to the business, operations and management of ports, where applicable.